2018
DOI: 10.1155/2018/7908148
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and Prognostic Validity of Proadrenomedullin among Neonates with Sepsis in Tertiary Care Hospitals of Southern India

Abstract: Introduction To evaluate Proadrenomedullin (Pro-ADM) as the diagnostic and prognostic marker in neonatal sepsis. Materials and Methods In this cross-sectional study, Pro-ADM levels were estimated in 54 neonates with clinical sepsis and positive sepsis screen (cases) and 54 controls without clinical sepsis. Repeat Pro-ADM levels were estimated after 72 hours in cases. Pro-ADM levels were compared with the clinical outcome. Results and Discussion Median Pro-ADM levels in cases were 31.8 (IQR: 27.8-39.4) pmol/ml … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Analysis of serum pro-ADM levels in the present study revealed that the sepsis group had a significantly higher mean pro-ADM level compared with the control group (mean=35.09 versus 10.58, respectively; P<0.001). This result is in agreement with earlier studies, which reported higher levels of pro-ADM in neonates diagnosed with bacterial infection [11][12][15][16].…”
Section: Discussionsupporting
confidence: 94%
“…Analysis of serum pro-ADM levels in the present study revealed that the sepsis group had a significantly higher mean pro-ADM level compared with the control group (mean=35.09 versus 10.58, respectively; P<0.001). This result is in agreement with earlier studies, which reported higher levels of pro-ADM in neonates diagnosed with bacterial infection [11][12][15][16].…”
Section: Discussionsupporting
confidence: 94%
“…90% of neonates with increased ProADM died and 92.5% of neonates with decreased ProADM survived. The serial monitoring of ProADM levels had a significant role in predicting prognosis: indeed, a decrease in ProADM level by 10 pMol/mL was associated with a 99% probability of survival [19].…”
Section: Neonatal Sepsismentioning
confidence: 99%
“…Sensitivity for the diagnosis of sepsis was 93.3%, and specificity 86.7% [ 144 ]. However, as ProADM serum values are higher in preterm than in term babies, better prediction of EOS depends on the use of different cut-off levels according to GA (3.9 nmol/L in term neonates and 4.3 nmol/L in preterm babies) [ 96 , 145 ]. Better results have been reported when ProADM was used in combination with other markers [ 146 ].…”
Section: Biomarkers Presently Used In Clinical Practicementioning
confidence: 99%